Factorise:-

(2p-3q)2 - (3p + 2q)2

 hi apoorva,

here we must use (a+b)and (a-b)

so we get {(2p)2 - 2(2p)(3q) + (3q)2} - {(3p)2 + 2(3p)(2q) + (2q)2

(4p2 - 12pq + 9q2) - (9p2 + 12pq + 4q2)

now if we remove the bracket we get

4p2 - 12pq + 9q2 - 9p2 - 12pq - 4q2

4p2 - 9p2 - 12pq + 9q2 - 4q2

-5p2 - 24pq + 5q2

hope it helps

  • 0

(2p -3q)2 -(3p +2q)2

=using (a-b)2 and (a+b)2 formulas

=4p2 +9q2 -12pq - (9p2 +4q2 +12pq)

=4p2 +9q2 -12pq -9p2 -4q2 -12pq

=-5p2 +5q2 -24pq

  • -2

 sorry...let me do it once again

(2p -3q)2 -(3p +2q)2

using (a2 -b2) = (a+b) (a-b)

=(2p- 3q+3p +2q) (2p -3q - 3p -2q)

=(5p-q) (-p -5q)

  • 1

the ans may be (2p-3q-3p-2q)(2p-3q+3p+2q)

  • 2
What are you looking for?